Urban Expansion, Climate Vulnerability, and Transportation Resilience: Insights for Sustainable Development - Arifai, Achmad Muhyidin; Arsyad, Muhammad Fahmi (Advance Sustainable Science Engineering and Technology, 2025)
Climate change poses a significant threat to transportation infrastructure, particularly in rapidly urbanizing regions like Bumi Serpong Damai (BSD) City, Indonesia, which faces increased risks of flooding and the urban heat island (UHI) phenomenon. However, limited research has assessed the combined impacts of climate and land use changes on infrastructure resilience. This study addresses this gap by integrating remote sensing analysis, climatological data, field observations, and stakeholder interviews to identify key vulnerabilities. The results highlight that low-lying and high-impermeability areas, such as the BSD highway and Central Business District (CBD), are highly susceptible to flooding and UHI effects. To enhance resilience, the study proposes structural, nature-based, and technology-driven adaptation strategies, including improved drainage, sponge city concepts, and IoT-based climate monitoring. These findings provide essential insights for urban planners and policymakers, emphasizing the need for climate-adaptive infrastructure planning and sustainable urban development policies.